2017
DOI: 10.1038/s41598-017-14894-9
|View full text |Cite
|
Sign up to set email alerts
|

Female mice lacking Pald1 exhibit endothelial cell apoptosis and emphysema

Abstract: Paladin (Pald1, mKIAA1274 or x99384) was identified in screens for vascular-specific genes and is a putative phosphatase. Paladin has also been proposed to be involved in various biological processes such as insulin signaling, innate immunity and neural crest migration. To determine the role of paladin we have now characterized the Pald1 knock-out mouse in a broad array of behavioral, physiological and biochemical tests. Here, we show that female, but not male, Pald1 heterozygous and homozygous knock-out mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…We next investigated the loss of Pald1 on VEGFR2 signalling in vivo using a global constitutive Pald1 knockout mouse (Wallgard et al , 2012). We examined murine cardiac endothelial cells as an example of microcirculatory endothelial cells responsive to VEGF‐A, moreover, heart endothelial cells express Pald1 and, in contrast to lung endothelial cells, they do not show an overt phenotype in the Pald1 −/− mouse (Wallgard et al , 2012; Egana et al , 2017; Schaum et al , 2018). Accordingly, VEGF‐A was injected into the tail vein of adult mice followed by retrieval and lysis of hearts at specific time points and immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the loss of Pald1 on VEGFR2 signalling in vivo using a global constitutive Pald1 knockout mouse (Wallgard et al , 2012). We examined murine cardiac endothelial cells as an example of microcirculatory endothelial cells responsive to VEGF‐A, moreover, heart endothelial cells express Pald1 and, in contrast to lung endothelial cells, they do not show an overt phenotype in the Pald1 −/− mouse (Wallgard et al , 2012; Egana et al , 2017; Schaum et al , 2018). Accordingly, VEGF‐A was injected into the tail vein of adult mice followed by retrieval and lysis of hearts at specific time points and immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…However, Paladin has been implicated in various cell signalling pathways. A broad phenotypic screen in Pald1 null mice covering all organ systems revealed a specific lung phenotype, i.e., an emphysema‐like lung histology and increased turnover of lung endothelial cells (Egana et al , 2017). In addition, studies on chick embryos support a role for Paladin in neural crest migration (Roffers‐Agarwal et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two aspects might explain why PALD1 had not been previously associated with Hh signaling: i) PALD1 is dispensable for Hh signal transmission in several tissues, as PALD1-deficient IMCD3 cells mount a partial response to Hh (Fig. 8) and Pald1 −/− mice only show a mild phenotype (German Mouse Clinic Consortium et al, 2017). ii) PALD1 is a cell-type specific factor that accumulates in primary cilia of select cell types in response to Hh signal.…”
Section: Resultsmentioning
confidence: 99%
“…Pald1, phosphatase domain containing paladin 1, is a regulator of angiogenesis and vascular function. Female Pald1 -/exhibit an emphysema-like lung disorder (Egaña et al, 2017). However, cell culture studies have shown Pald1 to have a role in insulin signaling by negatively regulating insulin receptor expression and phosphorylation (Huang et al, 2009).…”
Section: Geneticsmentioning
confidence: 99%